Crops and trees for function to the existing land use of Blongkeng sub watershed, Java, Indonesia - Kusumandari, Ambar (Penerbit Universiti Kebangsaan Malaysia, 2019)
Although the Government of Indonesia has the rule to state the land area function, however the existing land use could be improper to its function. The objective of this research is to study the suitability of the existing land use with the land area function and to assess the land suitability of several food crops and trees. This research was carried out in Blongkeng sub watershed. Observatory research method was applied and the parameters collected include slopes, soil type, and rainfall using maps. GIS was applied and data were analyzed using quantitative descriptive. In this study, matching method was used to define the fitness of the land unit for growing of such crops or trees. To recognize the land suitability, 12 parameters were analyzed. Blongkeng sub watershed has the area of 7,498.64 ha and consists of 92 land units and 9 land use types includes: mixed cropping, National Park, dry field, water, shrubs, settlement, grass, rice field, and dry rice field. The land area function is composed: 397 ha of protected (5.29%); 1,292.56 ha of buffer (17.24%); 1,265.51 ha of annual plant silvyculture (16.88%), and 4,543.58 ha of perennial crop and settlement (60.59%). The existing land use that is improper with the land area function was found in all land areas. Most of the existing land use of Blongkeng sub watershed area is suitable to the function of the land (83.65%) and the rest of the area (16.35%) is improper. The majority of the land units have the marginally suitable (S3) for zea mays, dry paddy field, rice field and cassava with the constraints of rainfall depth, soil texture, and soil solumn. Furthermore, soy bean and sweet potato can be promoted to be planted, however peanut is not suitable (N) for the area. The suitability of trees showed that all land units in annual plant silvyculture zone are marginally suitable (S3) for P. falcataria (sengon). Some of the land units are marginally suitable (S3) for coconut, jackfruit, papaya, guava, longan, mango, avocado, and mahogany. The constraints factors mostly are soil texture, slopes, and rainfall depth. So, the government should change their policy in managing the land properly.